Photoprotection behaviors among patients during retinoid therapy - Czechowska, Julia; Bronst, Paulina; Szabrańska, Anna; Laskowski, Jakub; Kister, Klaudia; Rosa, Lidia; Zach-Źródlak, Monika; Małolepsza, Aleksandra; Rektor, Natalia; Mazur, Magdalena (Journal of Education, Health and Sport, 2023)
Aim: The aim of the study was to examine patients on dermatology retinoid treatment attitudes related to skin protection against UV radiation and to check the hypothesis whether patients using retinoids are more aware of the need for photoprotection. Material and methods: Internet-based survey about attitudes associated with sun exposure and photoprotection was carried out between March and May 2023. 176 questionnaires were subject to statistical analysis. Results: The study showed that 73% of the responders used an SPF cream every day. Only 3,8 % didn’t use a UV protection cream. 38% used it on all the exposed body parts. 21% used it only on their face and necks and 10% used it only on their face. As many as 78% of respondents used a cream with protection SPF 50 or more. 40% of patients reapply SPF. Most of the patients use additional tools such as sunglasses, hats and caps. But only 16% use specialized UPF clothing. Conclusion: Patients during their retinoid treatment show increased knowledge and attitude towards photoprotection. They are aware of the risks due to sensitization of their therapy and are trying to mitigate the negative effects of the UV radiation.